Mealtime Assistance ... From Chaos to Calm: A Collaborative Best Practice Implementation Project. Issue 1 (January 2019) - Sykes, Pamela; Norris, Ian; Cook, Megan; Woods, Aaron; Boughton, Rachel; Chilcott, Kylie; Walsh, Kenneth
Abstract : Background: Providing appropriate and timely mealtime assistance to hospitalized patients should be part of a multifaceted and multidisciplinary approach to optimizing a patient's nutritional care plan. Problem: There was anecdotal evidence at the study hospital that patients did not receive adequate and/or timely assistance at mealtimes. Approach: A best practice implementation project, using a proven strategy of audit, feedback, and reaudit, was used to effect practice change on an acute general medical ward. Outcomes: The combined interventions of staff engagement, redesigning the model of care to reprioritize activities at mealtimes, clarifying nutritional care roles and responsibilities, introducing a protected mealtime and a novel 2-tiered colored tray system, and implementing an awareness and education program have resulted in significant improvements in mealtime assistance. Conclusions: Success of the project is considered to be replicable and sustainable hospitalwide and more broadly. Abstract : Supplemental Digital Content is Available in the Text.